Opioids and cerebral physiology in the acute management of traumatic brain injury: a systematic review. (16th April 2019) - Wiener, Joshua; McIntyre, Amanda; Janzen, Shannon; Mirkowski, Magdalena; MacKenzie, Heather M.; Teasell, Robert
ABSTRACT: Background : Following traumatic brain injury (TBI), optimization of cerebral physiology is recommended to promote more favourable patient outcomes. Accompanying pain and agitation are commonly treated with sedative and analgesic agents, such as opioids. However, the impact of opioids on certain aspects of cerebral physiology is not well established. Objective : To conduct a systematic review of the evidence on the effect of opioids on cerebral physiology in TBI during acute care. Methods : A comprehensive literature search was conducted in five electronic databases for articles published in English up to November 2017. Studies were included if: (1) the study sample was human subjects with TBI; (2) the sample size was ≥3; (3) subjects were given an opioid during acute care; and (4) any measure of cerebral physiology was evaluated. Cerebral physiology measures were intracranial pressure (ICP), cerebral perfusion pressure (CPP), and mean arterial pressure (MAP). Subject and study characteristics, treatment protocol, and results were extracted from included studies. Randomized controlled trials were evaluated for methodological quality using the Physiotherapy Evidence Database tool. Levels of evidence were assigned using a modified Sackett scale. Results : In total, 22 studies met inclusion criteria, from which six different opioids were identified: morphine, fentanyl, sufentanil, remifentanil, alfentanil, and phenoperidine. The evidence for individual opioids demonstrated equally either: (1) no effect on ICP, CPP, or MAP; or (2) an increase in ICP with associated decreases in CPP and MAP. In general, opioids administered by infusion resulted in the former outcome, whereas those given in bolus form resulted in the latter. There were no significant differences when comparing different opioids, with the exception of one study that found fentanyl was associated with lower ICP and CPP than morphine and sufentanil. There were no consistent results when comparing opioids to other non-opioid medications. Conclusion : Several studies have assessed the effect of opioids on cerebral physiology during the acute management of TBI, but there is considerable heterogeneity in terms of study methodology and findings. Opioids are beneficial in terms of analgesia and sedation, but bolus administration should be avoided to prevent additional or prolonged unfavourable alterations in cerebral physiology. Future studies should better elucidate the effects of different opioids as well as varying dosages in order to develop improved understanding as well as allow for tighter control of cerebral physiology. Abbreviations: CPP: Cerebral Perfusion Pressure, GCS: Glasgow Coma Scale, ICP: Intracranial Pressure, MAP: Mean Arterial Pressure, PEDro: Physiotherapy Evidence Database, RCT: Randomized Controlled Trial, TBI: Traumatic Brain Injury